Spontaneous rupture of flexor pollicis longus tendon by tendolipomatosis in proximal phalanx: A case report. Issue 37 (September 2018) - Lee, Young-Keun; Lee, Malrey
Abstract: Rationale: Spontaneous flexor pollicis longus (FPL) tendon rupture is rarely reported. Although there are several studies investigating spontaneous FPL tendon rupture, the exact etiology of spontaneous rupture is unclear. Here, we present a case of unusual spontaneous FPL tendon rupture due to tendolipomatosis. Patient concerns: A 64-year-old right-handed retired male teacher was referred to our clinic with an inability to flex the interphalangeal joint of his left thumb. Diagnosis: Magnetic resonance imaging (MRI) revealed complete FPL tendon rupture at the level of the distal one-third of the proximal phalanx. Interventions: With the patient under general anesthesia, the FPL tendon was explored through a volar zig-zag incision. During the operation, the FPL tendon was found to be ruptured completely. Gross examination revealed a slightly yellowish denaturated tissue at the distal end of the ruptured tendon. We excised the denaturated tissue from the distal end of the ruptured tendon and sent it for histological examination. FPL tendon was repaired primarily via modified Becker method. Histopathological examination revealed normal vasculature in the tendon tissue and degenerative changes associated with lipid deposits in the tendon tissue. Outcomes: At 12-month follow-up, the patient was completely asymptomatic and had excellent IP joint range of motion (0° to 40°) in his left thumb. The wrist grip strength was 30 kg (28 kg in the Rt.) and the thumb pinch strength was 5.7 kg (4.7 kg in the Rt.). The Quick DASH score was 0. Lessons: Spontaneous rupture of the FPL tendon, attributed to degenerative changes caused by tendolipomatosis, is the first report of its kind, in the authors' opinion. Hence we recommend to perform the histopathological examination of the debrided tissue from the ends of the ruptured tendon, if the physicians couldn't know the exact cause of the spontaneous intratendinous rupture of the FPL. And early diagnosis followed by debridement and primary tendon repair provides an effective outcome.